2002
DOI: 10.1007/s00066-002-0939-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Comparison of Conventional Three-Dimensional Radiotherapy and Intensity Modulated Radiotherapy in the Therapy of Locally Advanced Non-Small Cell Lung Cancer

Abstract: IMRT gives the possibility of further dose escalation without an increasing mean lung dose especially in patients with large tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
(71 reference statements)
0
20
0
Order By: Relevance
“…The intensity-modulated radiotherapy offers an opportunity of dose escalation and may provide another tool for improving local control and survival [20].…”
Section: Discussionmentioning
confidence: 99%
“…The intensity-modulated radiotherapy offers an opportunity of dose escalation and may provide another tool for improving local control and survival [20].…”
Section: Discussionmentioning
confidence: 99%
“…The advent of 3DCRT and consequent improvements in toxicity profiles also initiated a series of phase I and II dose-escalation trials that occurred in parallel with development of IMRT. Several authors showed that with the same dose constraints, up to 35% greater RT doses could be given to the target with IMRT than 3DCRT, with the aim of improving local control (23,25,57). Armed with this favorable dosimetric data on toxicity and significant improvements already demonstrated with 3DCRT, several institutions initiated dose-escalation trials in the 1990s and 2000s.…”
Section: Impact Of Heterogeneity Correctionmentioning
confidence: 99%
“…A proven method for improving the conformality of a dose distribution is intensity modulated radiation therapy (IMRT). ( 1 – 4 ) Clinicians are hesitant to treat non‐small‐cell lung cancer patients with IMRT, even though clinical studies have demonstrated that an escalation in radiation dose results in significant improvement in the outcome of these patients. ( 5 , 6 ) The reluctance is due to organ motion effects, including dose blurring effect and interplay effect (7) …”
Section: Introductionmentioning
confidence: 99%